2002
DOI: 10.1177/0038038502036001006
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Heroics: A Study of News Reports with Particular Reference to Gender

Abstract: Media portrayals of women with cancer emphasize women's emotionality in the face of life-threatening disease. For some sociological commentators, this weakens women in an exercise of patriarchal control by medicine and the media. The present study, of news reports of people with cancer in the media of several anglophone countries, compares portrayals of men and women. Media representations of the emotions of people with cancer are found to emphasize women's skills in the emotional labour of self-transformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0
7

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 22 publications
4
94
0
7
Order By: Relevance
“…The use of the LSS-based measures of stoicism suggests that men have higher levels of stoicism (Wagstaff & Rowledge, 1995), which is consistent with the traditional notion that stoicism is associated with being male (Fergus, Gray, Fitch, Labrecque, & Phillips, 2002;Seale, 2002) and older adult (Moore et al, 2013;Yong, 2006). Some authors have suggested that men and older adults are more stoical because it is harder for them to identify and express their emotions (Gaitniece-Putāne, 2006).…”
Section: Introductionsupporting
confidence: 70%
“…The use of the LSS-based measures of stoicism suggests that men have higher levels of stoicism (Wagstaff & Rowledge, 1995), which is consistent with the traditional notion that stoicism is associated with being male (Fergus, Gray, Fitch, Labrecque, & Phillips, 2002;Seale, 2002) and older adult (Moore et al, 2013;Yong, 2006). Some authors have suggested that men and older adults are more stoical because it is harder for them to identify and express their emotions (Gaitniece-Putāne, 2006).…”
Section: Introductionsupporting
confidence: 70%
“…I have reported on the psychological, characterological and emotional transformations portrayed in this sample of news reports in a further paper emerging from this research project (Seale 2001b …”
Section: Resultsmentioning
confidence: 99%
“…Death is not described in the context of expressions of love and the idealized completion of life's journey as the deaths of those dying of cancer appeared to have been in Seale's (2001Seale's ( , 2002) media analysis of cancer deaths. Religiosity seldom frames these stories.…”
Section: Discussionmentioning
confidence: 99%